What is the role of the pharmacist?: physicians' and nurses' perspectives in community and hospital settings of Santiago de Cuba - Niurka María Dupotey Varela; Djenane Ramalho de Oliveira; Caridad Sedeño Argilagos; Kisvel Oliveros Castro; Elisveidis Mosqueda Pérez; Yelina Hidalgo Clavel; Nelly Sánchez Bisset (Universidade de São Paulo, 2011)
This study was carried out to understand the perceptions and expectations of the other health care professionals about pharmacists' role in primary health care centers and hospitals in Santiago de Cuba (Cuba). A cross-sectional descriptive study was conducted, applying a self-administered questionnaire to health care professionals. The sample included 763 professionals (40.9% physicians and 59.1 % nurses) from hospitals and primary health care clinics, chosen by random stratified sampling,. The most common activity performed by pharmacists was the distribution of medications or the drug supply management (51.5%) and adverse drug reactions reporting (29.4%), activities performed daily by pharmacists. Pharmaceutical care practice was considered as poor by the professionals, and only 15.6% of them have collaborated in these programs in the past. For nurses and physicians, interprofessional communication occurs sometimes (56.9%) and never (25.8%). Pharmacists' integration into the health team was considered as fair (50.7%). A total of 70.1% perceived the pharmacist as a drug expert and 60.1% as a professional who provides medication counseling. The main expectations these health care professionals expressed were that pharmacists provide more education about medication (97.4%) and improve their interprofessional communication techniques in order to communicate more effectively with the other members of the health care team (96.6%). O presente trabalho analisa o papel do farmacêutico na atenção primária de saúde e em hospitais, na percepção de profissionais da saúde na província de Santiago de Cuba. Um estudo descritivo transversal foi conduzido, através da aplicação de um questionário autoadministrado a uma amostra de 763 profissionais de atenção primária e hospitalar, 40,9% de médicos e 59,1% de enfermeiros. As funções farmacêuticas mais reconhecidas pelos profissionais desta amostra foram o fornecimento e distribuição de medicamentos (51,5%) e o relato de reações adversas medicamentosas (29,4%), funções desenvolvidas diariamente. A prática da atenção farmacêutica é limitada na percepção dos profissionais e apenas 15,6% têm participado em programas desse tipo. Comunicação interprofissional ocorre às vezes (56,9%) e nunca (25,8%), com maiores dificuldades na atenção primária de saúde. A integração do farmacêutico na equipe de saúde foi considerada regular (50,7%). Um total de 70,1% dos profissionais percebeu o farmacêutico como especialista em medicamentos e 64,1% como o profissional que aconselha sobre o uso de medicamentos. As principais expectativas colocam-se na necessidade de que o farmacêutico ofereça educação sobre o uso de medicamentos (97,4%) e reforce as suas técnicas da comunicação na equipe multidisciplinar (96,6%).